Contagious you : unlock your power to influence, lead, and create the impact you want - Cavanaugh, Anese (Business professional collection, 2020)
"The quality of our leadership all starts with our individual intentions, energy, presence, self-care, and choices. Drawn from Cavanaugh's proprietary approach to leadership, Intentional Energetic Presence® (IEP Method®), Contagious You shows you how to "own" your leadership and effectively guide, inspire, and serve those around you. Insightful stories and real-life examples address the areas of team, dealing with failure, leading and changing culture, designing relationships, navigating conflict, transforming burnout, cultivating mindset, and more. This book is essential reading for anyone looking to foster connection, achieve great results, and become a force for good in the world. Synopsis This insightful guide from the creator of the IEP Method® (Intentional Energetic Presence®) provides individuals at any stage in their careers the tools and inspiration to show up as a dynamic and positively contagious leader"--